Multisystem inflammatory syndrome in children during the first two years of the COVID-19 pandemic in Luxembourg - Ooms, C.; Mossong, J.; Vergison, A.; Biver, A.; Wagner, K.; Niel, O.; Parrish, A.; Abdelrahman, T. T.; de la Fuente Garcia, I. (Frontiers in Pediatrics, 2023)
Objective Estimate the incidence of multisystem inflammatory syndrome (MIS-C) in children (0–15 years), the role of SARS-CoV-2 variants during the first two years of COVID-19 pandemic in Luxembourg; and describe the demographic, biological and clinical characteristics of the patients. Method Observational retrospective cohort study. Cases between March 2020 and February 2022 were ascertained from the national registry of MIS-C cases by a retrospective review of medical records. Reported SARS-CoV-2 infections were obtained from the national COVID-19 surveillance system. We calculated monthly MIS-C incidence, the ratio between MIS-C and SARS-CoV-2 infections and associated rate ratios by the periods corresponding to the circulation of different variants. Results 18 children were diagnosed with MIS-C among 35,200 reported infections. The incidence rate of MIS-C was 7.2 [95% confidence interval (CI) 4.5–11.4] per 1,000,000 person-months. A higher incidence of MIS-C was observed between September and December 2021, corresponding to the circulation of the Delta variant than during the first year of the pandemic (RR 3.6, 95% CI, 1.1–12.3). The lowest rate of MIS-C per infection was observed during the Omicron (RR 0.17, 95% CI, 0.03–0.82). Median age at diagnosis was 6.5 years. Previously healthy children made up 88% of MIS-C cases, none were vaccinated against SARS-CoV-2. 33% required intensive care. All patients recovered fully. Conclusions MIS-C incidence and MIS-C risk per infection changed significantly over time during the first two years of COVID-19 pandemic. Monitoring of MIS-C incidence in future SARS-CoV-2 waves will be essential to guide public health interventions and vaccination policies for children.